Convergence Evaluation of a Load Flow Method based on Cespedes' Approach to Distribution System Analysis - Diego Issicaba; Jorge Coelho (Institute of Advanced Engineering and Science, 2016)
This paper evaluates the convergence of a load flow method based on Cespedes' formulation to distribution system steady-state analysis. The method is described and the closed-form of its convergence rate is deduced. Furthermore, convergence dependence of loading and the consequences of choosing particular initial estimates are verified mathematically. All mathematical results have been tested in numerical simulations, some of them presented in the paper.